Music theory through improvisation : a new approach to musicianship training - Sarath, Ed (New York : Routledge, 2010)
Accompanying CD-ROM includes: audio files
"Music Theory Through Improvisation presents a unique approach to basic theory and musical training, examining the study of traditional theory through the art of improvisation. The book follows the same general progression of diatonic to non-diatonic harmony in conventional approaches, but integrates improvisation, composition, keyboard harmony, analysis, and rhythm. Geared toward the diverse interests and abilities of today's student, Music Theory Through Improvisation places the study of harmony within improvisation and composition in stylistically diverse formats, including jazz and popular music. Keyboard realization, for students with little or no keyboard training, is the primary mode of assimilation of harmonic materials"--Back cover
-- Improvisation across boundaries : a trans-stylistic approach -- Music fundamentals -- Modality and rhythm I : time feels -- Modality and rhythm II : small group framework -- Basic tonal materials : triads and seventh chords -- Harmonic functions -- Swing : gloval rhythmic gateway -- Melodic line construction and harmonization -- Chord inversion present and past -- Non-diatonic harmony I : applied chords -- Non-diatonic harmony II : modal mixture -- Figured bass realization at the keyboard -- Extended chords -- Altered extensions -- Diverse approaches to analysis -- Fine-tuning and expanding the jazz palette
Includes bibliographical references and index
Keywords: Music theory; Jazz -- Instruction and study; Improvisation (Music)